Improvement of Speaking Skills Using Role-Playing Method - Eka Safitri; Akhmad Tabrani (STAI Miftahul Ula Nganjuk, 2023)
This study aims to provide an overview and explanation of: 1) Students' interest in learning speech skills, specifically speech material, using the role-playing method; 2) The level of students' involvement in learning speech skills, particularly speech material, using the role-playing method; and 3) Students' proficiency in learning speech skills, especially in delivering speeches, using the role-playing method. The research method employed is Classroom Action Research (CAR) conducted in class XI BDP Pi at SMK Sunan Kalijogo Malang. Data collection techniques in this study involved observation and tests. The subjects consisted of 32 students in class XI BDP Pi at SMK Sunan Kalijogo Malang. Based on the research results, during the preliminary cycle, only 7 out of 32 students, or 21.87%, passed the speech proficiency test. After implementing actions in the first cycle, the number of proficient students increased to 14, or 43.75%. In the second cycle, the number of proficient students significantly increased to 28, or 84.22%. In conclusion, the use of the role-playing method effectively enhances students' speech skills in delivering speeches within class XI BDP Pi at SMK Sunan Kalijogo Malang. In teaching speech skills, a teacher should be active and skilled in selecting teaching aids to prevent students from becoming disengaged during the learning process.